2013
DOI: 10.1037/a0031666
|View full text |Cite
|
Sign up to set email alerts
|

Missing link in the service profit chain: A meta-analytic review of the antecedents, consequences, and moderators of service climate.

Abstract: Service climate captures employees' consensual perceptions of organizations' emphasis on service quality. Although many studies have examined the foundation issues and outcomes of service climate, there is a lack of a comprehensive model explicating the antecedents, outcomes, and moderators of service climate. The current study fills this void in the literature. By conducting a meta-analysis of 58 independent samples (N = 9,363), we found support for service climate as a critical linkage between internal and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
433
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(458 citation statements)
references
References 176 publications
(244 reference statements)
22
433
2
1
Order By: Relevance
“…Intrinsically motivated project members are also likely to be more effective in interacting with and influencing targets. Related research on service organizations and the service-profit chain reports positive emotional and productivity spillover effects such that intrinsically motivated, committed, and satisfied staff have higher quality interactions with customers leading to more loyal and satisfied customers and higher firm performance (S. P. Brown & Lam, 2008;Hong, Liao, Hu, & Jiang, 2013).…”
Section: Organizational Practices As Enablersmentioning
confidence: 99%
“…Intrinsically motivated project members are also likely to be more effective in interacting with and influencing targets. Related research on service organizations and the service-profit chain reports positive emotional and productivity spillover effects such that intrinsically motivated, committed, and satisfied staff have higher quality interactions with customers leading to more loyal and satisfied customers and higher firm performance (S. P. Brown & Lam, 2008;Hong, Liao, Hu, & Jiang, 2013).…”
Section: Organizational Practices As Enablersmentioning
confidence: 99%
“…They found that unit-level customer orientation climate moderated the relationship such that customer-oriented employees exhibited more customer-oriented behaviors when the unit-level customer orientation climate was high; in turn, unit-level customer orientation behaviors were positively related to unit-level performance. A recent meta-analysis of 58 samples found that service climate was related to operational and organizational performance (Hong et al 2013). This research shows the multilevel (employee and unit level) linkages between service orientation, performance, and outcomes.…”
Section: Customer Servicementioning
confidence: 99%
“…The communicative and symbolic consequences of TMT heterogeneity are likely to increase employees' assessments of its credibility (Kim, Bateman, Gilbreath, & Andersson, 2009;Mayer & Gavin, 2005), which can foster an organisation's climate of productive energy (Raes et al, 2013), in the process improving lower echelons' perceptions of fairness, diversity and trust and, ultimately, leading to greater responsiveness and engagement (Schneider, Ehrahrt, & Macey, 2013). The more open and participative organisational climates generated by the symbolic and communicative consequences of heterogeneous TMTs also appear to better align the styles and practices of line managers in support to wider organisational strategies (Raes et al, 2011), emphasising the crucial 'linking pin' role that line managers play both in strategy formulation and implementation (Wooldridge, Schmid, & Floyd, 2008), the latter specifically relevant to overall staff engagement and commitment (Hong, Liao, Hu, & Jiang, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Where HRM policies are concerned, for example, employees will, to a growing extent, be those delivered or enacted by line managers, especially front line managers with direct supervisory responsibility' (p. 3). In this way, line managers play a crucial role determining the extent to which lower level staff are engaged with and committed to the wider strategies and policies of the organisation (Hong, Liao, Hu, & Jiang, 2013). Important here is the way line managers communicate policies to staff and also their leadership styles, in terms of fairness towards staff and levels of support.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%